2023
DOI: 10.1371/journal.pone.0286452
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate regression modelling for gender prediction using volatile organic compounds from hand odor profiles via HS-SPME-GC-MS

Abstract: The efficacy of using human volatile organic compounds (VOCs) as a form of forensic evidence has been well demonstrated with canines for crime scene response, suspect identification, and location checking. Although the use of human scent evidence in the field is well established, the laboratory evaluation of human VOC profiles has been limited. This study used Headspace-Solid Phase Microextraction-Gas Chromatography-Mass Spectrometry (HS-SPME-GC-MS) to analyze human hand odor samples collected from 60 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Female chamber odor samples depicted a tighter clustering, except for one female. These observations further corroborate the previous literature delineating differences in volatile odor signatures as a function of gender [23,24,30]. Corroborating the results from Pojmanova et al, it is important to note that quantitative differences in each individual compound are not as important as the comprehensive group of VOCs and their representative amounts [39], especially when discussing sex differentiation.…”
Section: Whole-body Samplingsupporting
confidence: 88%
“…Female chamber odor samples depicted a tighter clustering, except for one female. These observations further corroborate the previous literature delineating differences in volatile odor signatures as a function of gender [23,24,30]. Corroborating the results from Pojmanova et al, it is important to note that quantitative differences in each individual compound are not as important as the comprehensive group of VOCs and their representative amounts [39], especially when discussing sex differentiation.…”
Section: Whole-body Samplingsupporting
confidence: 88%
“…Studies have shown that the human skin volatilome is influenced by gender. , Our group, along with others have shown a differences in recovered abundances of medium and long-chain FAs between males and females. Increased abundances of aldehydes and ketones in male participants have also been reported compared to females .…”
Section: Resultssupporting
confidence: 58%
“…Machine learning (ML) and multivariate statistical approaches are now routinely employed for the analysis of human volatilomics to include skin as well as breath emissions. Both unsupervised, such as principal component analysis (PCA) , and hierarchical clustering (HCA) which have discriminatory power, and supervised learning, such as multiple linear regression (MLR), partial least-squares-discriminant analysis (PLS-DA), linear discriminant analysis (LDA), others, ,, which allow classification have been frequently used. These approaches allow for analysis through reducing dimensionality and aid in discrimination, clustering, classification and correlation of VOCs that may be linked to disease ,, and other physiological factors. , …”
Section: Introductionmentioning
confidence: 99%